Propuesta de mejora para las pinturas multipropósito de Alfachem S.A.S. (2016)
In this work proposals for improvement the properties if paints or anticorrosive coatings from alfachem are studied base on literature review of recent advances of some inhibitors and additives, selectin one that provides better properties to paints of such polyaniline which was evaluated at laboratory scale since its synthesis to incorporating this in the formulation of a primer.